An overview of phthalate acid ester pollution in China over the last decade: Environmental occurrence and human exposure - Gao, Dawen; Li, Zhe; Wang, He; Liang, Hong (The Science of the total environment, 2018)
The toxicity and bioaccumulation potential of phthalate acid esters (PAEs) make their impact on the environment a matter of considerable concern. Due to China's recent economic development and population growth, it has become one of the largest manufacturers and consumers of PAEs, with an associated contamination threat to several environmental compartments. The aim of this overview is to present a systematic account of PAE occurrence in various environmental media in China in the last decade, including the air, surface water, sediments, soil, sewage, and sludge; human exposure to PAEs is also evaluated. This reveals a location-dependence that can be attributed to regional differences in economic and industrial development as well as specific geographic location. A need for further study into the transportation and transformation behavior of PAEs in different environmental media and into PAE control technologies is identified, as a means of effectively assessing potential ecological and health risks. [Display omitted] •PAEs were detected ubiquitously and abundantly in China.•DEHP was the most abundant phthalates in various environmental media.•PAEs concentrations exhibit a location dependent.•Limited treatment might cause the widespread contaminations of PAEs.